2009
DOI: 10.5143/jesk.2009.28.4.125
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and Standing Action Analysis for Electric Adjustable Bed

Abstract: Recently, the frequency in use of electric adjustable bed is going up by an increase in the elderly population. In bad ergonomic design for an electric adjustable bed causes some problems in the aspects of usability and safety. In particular, lots of accidents came from going up or going down an electric adjustable bed. In that case, the height of bed is very important factor for preventing an accident. This problem is related to its anthropometric factors. Therefore we carried out its anthropometric analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Although, studies using anthropometric measurements for the design of electronics, furniture and clothes are activated, not many studies applying the measurements to workplace design are found (Jeong and Park, 1990;Gouvali and Boudolos, 2006;Jung et al, 2007;Kang and Jung, 2009;Jung et al, 2009;Daruis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although, studies using anthropometric measurements for the design of electronics, furniture and clothes are activated, not many studies applying the measurements to workplace design are found (Jeong and Park, 1990;Gouvali and Boudolos, 2006;Jung et al, 2007;Kang and Jung, 2009;Jung et al, 2009;Daruis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%